Outcomes of additional substrate modification in de novo atrial fibrillation ablation. (3rd October 2022) - Aslam, F; Al-Sadawi, M A; Aleem, S; Ijaz, H; Jacob, R; Cao, K; Santore, L; Almasry, I; Singh, A; Fan, R; Rashba, E
Abstract: Background: Pulmonary vein isolation (PVI) is the cornerstone of atrial fibrillation (AF) ablation. Data regarding additional substrate modification has been conflicting, both in paroxysmal and persistent atrial fibrillation. Purpose: To assess the effect of additional linear substrate modification during de novo AF ablation on AF recurrence. Methods: We reviewed 1575 AF ablations in 1254 patients from January 2013 to June 2021 at a single academic medical center. There were 1096 de novo ablations. We defined substrate modification as linear ablations including cavotricuspid isthmus (CTI), superior vena cava isolation, intercaval line, mitral isthmus, and left atrial roof and floor lines. We evaluated clinical and procedural characteristics to identify risk factors for AF recurrence and complications. Patients were followed for a minimum of 6 months. Results: The 1096 de novo ablations included 65.5% males with mean age 61.1 years, mean BMI 31.3, 81.8% paroxysmal AF and 18.2% persistent AF. There were four AF ablation subgroups: PVI alone (41.6%), PVI and CTI ablation (37.1%), PVI with CTI and additional substrate modification (15.6%), and PVI with substrate modification without CTI ablation (5.7%). Overall, AF recurred in 36.9% cases. AF recurrence with PVI only ablation was 41% compared to 32.7% in patients with PVI and CTI ablation (p=0.02). When looking at patients with paroxysmal and persistent AF, results were similar, with decreased AF recurrence with the addition of CTI ablation in both paroxysmal (37.3% v. 29.2%, p=0.03) and persistent AF (58.1% v. 40.0%, p=0.02). Additional substrate modification did not result in significant difference in outcome in either paroxysmal or persistent AF (Figure 1). Conclusions: In de novo AF ablations, addition of CTI ablation to de novo PVI ablation is associated with lower AF recurrence in both paroxysmal and persistent AF. Additional linear substrate modification did not impact outcomes. Funding Acknowledgement: Type of funding sources: None.